Factors Affecting the Cropping Patterns in Hills and Plains of the Central Development Region - Shrestha, Raj Man (Nepal Journal of Science and Technology, 2010)
Due to expansion of urbanization, introduction of advanced technology in the agriculture systems and low returns in traditional farming systems, farmers of the Central Development Region of Nepal were compelled to change the traditional farming systems to modern systems. The present study aims to find out the factors that affected the changes in cropping patterns in hills and plains of this region and develop statistical models to explain these changes. Primary data were collected from key persons residing in the villages of four districts (Kavrepalanchowk, Bhaktapur, Chitawan and Parsa) Region under multistage sampling technique. Causal factors such as plot size, distance from market centre, family size, profit and market opportunities had significant effects while other two factors, education and irrigation had insignificant effects on the changes in cropping patterns in the region. Plot size and distance had negative effects on change in cropping patterns from modern to traditional. Profit factor had significant effect on change in cropping patterns in Terai, whereas family size had significant effect on change in the hills of the Central Development Region. Key words: Farming systems; Multistage sampling; Modern crops; Traditional crops DOI: 10.3126/njst.v10i0.2961 Nepal Journal of Science and Technology Vol. 10, 2009 Page: 199-203